2024
DOI: 10.3389/fncel.2024.1369730
|View full text |Cite
|
Sign up to set email alerts
|

β-carbolines that enhance GABAA receptor response expressed in oligodendrocytes promote remyelination in an in vivo rat model of focal demyelination

Abraham Jotssel Cisneros-Mejorado,
Rainald Pablo Ordaz,
Edith Garay
et al.

Abstract: Demyelination is typically followed by a remyelination process through mature oligodendrocytes (OLs) differentiated from precursor cells (OPCs) recruited into the lesioned areas, however, this event usually results in uncompleted myelination. Potentiation of the remyelination process is an important target for designing effective therapeutic strategies against white matter loss. Here, it was evaluated the remyelinating effect of different β-carbolines that present differential allosteric modulation on the GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 61 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…In the cerebral cortex ( mctx ), β-CCB did not have a clear effect, whereas in some areas of the hippocampus it exhibited a mild effect. Thus, the promyelinating character of β-CCB was confirmed in a model of generalized demyelination, supporting the idea that β-carbolines have the potential to be used as therapeutic drugs against demyelinating diseases, as it has been shown elsewhere 12 , this promyelinating action could be explained by its potentiating effect on the oligodendroglial GABA A R.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…In the cerebral cortex ( mctx ), β-CCB did not have a clear effect, whereas in some areas of the hippocampus it exhibited a mild effect. Thus, the promyelinating character of β-CCB was confirmed in a model of generalized demyelination, supporting the idea that β-carbolines have the potential to be used as therapeutic drugs against demyelinating diseases, as it has been shown elsewhere 12 , this promyelinating action could be explained by its potentiating effect on the oligodendroglial GABA A R.…”
Section: Introductionsupporting
confidence: 72%
“…Previous studies have shown that β-CCB potentiates the response of GABA A Rs expressed in OPCs and OLs in culture, and that it has a promyelinating effect in a model of focal demyelination of the rat icp 3 , 5 , 8 , 12 . Identification of white matter structures that seem to undergo CPZ-induced demyelination, as assessed by MRI metrics and histology, allowed us to evaluate a generalized promyelinating effect of β-CCB.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations